Surface modification methods of plastic components produced by additive manufacturing: a review - Ficzere, Péter; László, Noémi (Design of Machines and Structures, 2023)
Additive manufacturing (AM) is a widely used process today, especially for the production of complex parts that cannot be produced with traditional material removal technologies. However, in the case of components produced by 3D printing, due to the specifics of the technology, poor surface quality is often to be expected. From the point of view of the product and production process, the so-called textural characteristics, surface roughness can be considered the most critical component. The surface of the part produced by 3D printing must meet several criteria (e.g., mechanical, physical, tribological, aesthetic, etc.). This article discusses the possibilities of surface modification of polymer parts produced with additive manufacturing technology, focusing on their effects on surface roughness. The paper also deals with the features suitable for describing the surface texture of 3D printed parts and their role in the characterization of printed parts.